2020
DOI: 10.3855/jidc.12341
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia in sepsis: analysis of the subcellular distribution of Ca2+ in septic rats and LPS/TNF-α-treated HUVECs

Abstract: Introduction: Hypocalcemia has been widely recognized in sepsis patients. However, the cause of hypocalcemia in sepsis is still not clear, and little is known about the subcellular distribution of Ca2+ in tissues during sepsis. Methodology: We measured the dynamic change in Ca2+ levels in body fluid and subcellular compartments, including the cytosol, endoplasmic reticulum and mitochondria, in major organs of cecal ligation and puncture (CLP)-operated rats, as well as the subcellular Ca2+ flux in HUVECs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…This hypothesis is supported by the fact that the administration of a calcium channel blocker results in a better prognosis and a reduction in mortality rates of septic patients [35]. These data corroborate with experimental findings; the administration of verapamil in septic animals resulted in a reduction of mortality, attenuation of cardiac lesions, reduction of intracellular calcium concentration, and attenuation of hypocalcemia [31,32,36]. The data from the present study also supports this hypothesis, as septic animals treated with verapamil survived longer than septic animals without treatment.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This hypothesis is supported by the fact that the administration of a calcium channel blocker results in a better prognosis and a reduction in mortality rates of septic patients [35]. These data corroborate with experimental findings; the administration of verapamil in septic animals resulted in a reduction of mortality, attenuation of cardiac lesions, reduction of intracellular calcium concentration, and attenuation of hypocalcemia [31,32,36]. The data from the present study also supports this hypothesis, as septic animals treated with verapamil survived longer than septic animals without treatment.…”
Section: Discussionsupporting
confidence: 69%
“…A previous study from our research group showed an increase in [Ca 2+ ] i in cultured neonatal cardiomyocytes treated with septic animal serum [31]. Calcium overload by CLP has also been demonstrated in the heart, brain, liver, and spleen cells of septic rats [32]. The hypotheses for this increase in [Ca 2+ ] i involve failures in the channels that regulate the entry of Ca 2+ , microruptures in the plasma ) groups were measured 6, 12, and 24 hours after CLP surgery and expressed in arbitrary units (AUs).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Indeed, iron binding by specific chelators was found to be effective in a number of cases of sepsis, and, moreover, iron chelation specifically altered the microbiota profile [ 55 , 56 ]. The same relates to disorders of calcium homeostasis in infections and sepsis, which are manifested in a decrease in Ca 2+ concentration in the blood and its overload in cytosol and mitochondria [ 33 , 34 , 35 ]. As follows from our data, each of these factors enhances the effect of microbial metabolites on mitochondrial membrane permeability almost tenfold, reducing their active concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in Ca 2+ levels in bodily fluids and subcellular compartments were found in different sepsis models. They were manifested in a decrease in the blood Ca 2+ concentration and calcium overload in cytosol, endoplasmic reticulum and mitochondria [ 32 , 33 , 34 ]. Moreover, it has been shown that the inhibition of mitochondrial permeability transition by cyclosporine A prevented sepsis-induced myocardial dysfunction and mortality [ 35 ].…”
Section: Introductionmentioning
confidence: 99%